Avaliação espaço-temporal da qualidade da água do reservatório da UHE Capivari-Cachoeira e corpos hídricos relacionados: uma abordagem de longo prazo - Lopes, Sarah Meier (2019)
Population growth triggers widespread use of water for a variety of purposes, such as: public supply, irrigation, and power generation. For example, the formation of reservoirs may cause changes in the natural conditions of the water bodies, triggering a series of changes in the limnological characteristics of the dammed water and downstream of it. Thus, the objective of the present study was to analyze the water quality of the Capivari-Cachoeira Hydroelectric Power Plant reservoir, located in the state of Paraná, as well as of the water bodies related to the project, based on longterm monitoring data. The study area covers the Capivari river and the Patos river upstream of the reservoir, the Capivari-Cachoeira reservoir, and the Cachoeira river, downstream of the reservoir. For the analyzes, the 11 years monitoring data was used, in five sampling stations located in the reservoir and in the rivers previously mentioned. Statistical analysis techniques were used to evaluate these data. The results showed that the water bodies upstream of the reservoir presented more degraded water quality when compared to the reservoir and the downstream points. This result is related to anthropic activities of the environment, as well as the conditions of the reservoir that promote a higher sedimentation of phosphorus and suspended solids, reducing their values also downstream. The sampling station of the reservoir is the one that differs more spatially in relation to the others. The upstream stations located on the Capivari River and Patos River are more similar to each other, as well as downstream. All sampling stations, with the exception of the reservoir, had the lowest temperatures and the highest values of dissolved oxygen in the winter. The reservoir has distinct characteristics, such as stratification processes, which may explain its distinct pattern.The reservoir presented a warm monomictic circulation pattern, with a complete winter mix, interfering with the physical, chemical and phytoplanktonic elements. The dominance of the functional morphological group represented by the large colonial mucilaginous chlorophytes/cyanobacteria allowed to conclude that this reservoir has availability of nutrients and light. In addition to the pattern of circulation of the reservoir, it benefits the dominance of this group of organisms.